FROM THE OBSERVATIONS OF CEREMONIAL LEXICAL PARALLELS IN UKRAINIAN AND BULGARIAN DIALECTS SPREAD IN THE SOUTHERN BESSARABIA - Делюсто, Марина (Linguistic Bulletin (Movoznavchyi Visnyk), 2019)
The investigation of family rites gathered from different bearers of the Ukrainian and Bulgarian dialects spoken in the Southern Bessarabia is very actual nowadays, because of their existing in multilingual and multiethnic surroundings (besides Ukrainians and Bulgarians, Russians, Moldavians, Gagauzes live here). The representatives of different nationalities of this region during two hundred years common existing saved and shared with each other of unique elements of language and culture, they also created some integral units, which origin are defined difficulty. The purpose of the analysis is to describe lexical parallels of family rites in the Ukrainian and Bulgarian dialects of investigating region, to determine integral and different units in Ukrainian and Bulgarian languages, which became a result of these ethnic groups’ language and culture common existing and interaction on this territory. Results. The author comes to the conclusion that ceremonial terminological system of Ukrainians and Bulgarians in the Southern Bessarabia – multi-lingual lateral Ukrainian area between the Danube and the Dniester rivers – naturally is characterized by a lot of common lexical elements, at the same time there are many different units which caused by peculiarities of language or cultural part of definite ethnic group (compare Ukr. borsch, svi| tylky, z|myvky, poro| dillya and Bulg. | kuklichka, |malka | pita, gu| lyama | pita); from the other side some different lexemes are cuased by interlanguage / interdialectal interference (compare Rom. nanashu| ly, | zestra; Turk. kavar|ma, kur| ban). Originality. In contrast to other descriptions of interference process of lexical level of Ukrainian and Bulgarian languages in this area (I. Tsyganok, D. Kiosyeva) the author extents the list of lexical groups under consideration, besides it, he comes to the conclusion that Bulgarian dialects are also characterized by a lot of formal and semaintic variants. Conclusion. Further investigation of rites and ritual acts nomination of Ukrainian and Bulgarian dialects spread in the Southern Bessarabia will give the material for description of area variation of regional lexis through the prism of traditional culture. Gathered common patterns will become the basis of maps for «Multi-lingual atlas of dialects spread between the Danube and the Dniester rivers»